El código Da Vinci - Brown, Dan, 1964-; Calley, John.; Grazer, Brian, 1953-; Hanks, Tom.; Howard, Ron, 1954-; Mckellen, Ian.; Tautou, Audrey; Columbia Pictures; Imagine Entertainment (Firma); Sony Pictures Home Entertainment ([United States] : Sony Pictures Home Entertainment, 2006)
Un asesinato dentro del museo y las pistas en las pinturas de Da Vinci, conducen al descubrimiento de un misterio religioso protegido por una sociedad secreta por dos mil años que podrían quebrantar las bases del cristianismo.
Based on the novel by Dan Brown.
Special features: "First day on the set with Ron Howard" featurette; "A discussion with Dan Brown" featurette; "A portrait of Langdon" featurette; "Who is Sophie Neveu?" featurette; "Unusual suspects" featurette; "Magical places" featurette; "Filmmaker's journey" a two-part featurette; "Close-up on the Mona Lisa" featurette; "The codes of 'The Da Vinci code'" featurette; "The music of 'The Da Vinci code' featurette; 'The da Vinci code' puzzle game PC demo.
Screenplay by Akiva Goldsman ; director of photography, Salvatore Totino ; music by Hans Zimmer.
Tom Hanks, Audrey Tautou, Ian Mckellen.
MPAA rating: PG-13; for disturbing images, violence, some nudity, thematic material, brief drug references and sexual content.
DVD, NTSC; region 1, widescreen (2.40:1) presentation.
Keywords: Misterio -- Largometraje para televisión; Película de suspenso -- Largometraje para televisión